Hubungan Citra Tubuh Dengan Kualitas Hidup Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisis - Oxtavia, Vivi -; -, Jumaini -; Lestari, Widia - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Hemodialysis would affect body image and have the impact on quality of life of patients due to variety changes in the patients body. The purpose of this study was to determine the relationship between body image and quality of life of patients with chronic renal failure undergoing hemodialysis. The research method is descriptive correlative with cross sectional approach. The study was conducted in Arifin Achmad Hospital Pekanbaru with a sample of 60 respondents. The sampling method is purpossive sampling. Data collection tool in this study is a questionnaire with 40 statements. Data was analyze by using univariate and bivariate analysis using with chi square tests. The results showed that there is a relathionship between body image and quality of life of patients with chronic renal failure undergoing hemodialysis with p value (0,003) < α (0,05). This study recommend hemodialysis unit to further improve performance in providing comprehensive care nursing practice both physical and psychosocial in patients with chronic renal failure undergoing hemodialysis especially on the subject of body image disturbance that will affect the quality of life of patients. Keywords : Body image, chronic renal failure, hemodialysis, quality of life.